Chinese police officers' attitudes toward domestic violence interventions: do training and knowledge of the Anti-Domestic Violence Law matter?. (9th August 2021) - Lin, Kai; Sun, Ivan Y.; Wu, Yuning; Xue, Jia
ABSTRACT: In March 2016, China's Anti-Domestic Violence Law became effective. The main objective of this study is to empirically test the effects of training and knowledge on the recent anti-domestic violence legislation on Chinese police officers' attitudes toward law enforcement interventions into domestic violence. Performing Path Analysis on survey data collected from 623 police officers in Jiangsu, China, this study found that training and knowledge on the law, while mediating the positive effects of organisational support and previous experience of handling domestic violence on officers' proactive attitudes toward policing domestic violence, did not have a direct connection to pro-arrest attitudes. Organisational support is the strongest predictor of endorsement of domestic violence interventions as important police work and pro-arrest attitudes. Implications for criminal justice policies and practice are also discussed.